The association of race with time to severe liver disease diagnoses - Andrew D. Schreiner; Jingwen Zhang; Mulugeta Gebregziabher; Justin Marsden; Patrick D. Mauldin; Don C. Rockey (PLoS ONE, 2025)
Background Evidence suggests that there are racial differences in liver fibrosis progression for patients with chronic liver disease (CLD). We examined the association of Black race with the time to diagnosis of severe liver disease outcomes in primary care patients. Methods We captured electronic health record data from a primary care clinic between 2012−2021. Race, categorized as Black and non-Black, was the primary exposure. The outcome was the occurrence of a severe liver event identified by ICD-9/10 codes, defined as a composite of cirrhosis, complications of cirrhosis, hepatocellular carcinoma, and liver transplantation. Cox regression models evaluated the association of Black race with the time to severe liver outcomes while adjusting for potentially confounding covariates. Results The cohort included 20,828 patients of whom 43% identified as Black and 14% had a known diagnosis of CLD during follow-up. Of all patients, 3% received a diagnosis code for a severe liver event. In an unadjusted Cox regression model, Black race was associated with an increased hazard of a severe liver event (HR 1.32; 95%CI 0.98–1.34), but after adjusting for known CLD, baseline fibrosis risk, demographic, and comorbidity variables, Black race was associated with a significantly lower hazard of a severe liver outcome (HR 0.68; 95%CI 0.57–0.81). Conclusions After adjusting for potentially confounding covariates, Black race was associated with a longer time to a severe liver disease diagnosis. This finding raises the possibilities of delayed cirrhosis detection or differences in liver fibrosis progression by racial identifiers.